STUDENTS’ PERCEPTIONS ON REPEATED READING AND READING FLUENCY IN ENGLISH CLASS - Paskalina Widiastuti Ratnaningsih (Al-Irsyad: Journal of Education Science, 2025)
As one of the main skills in English, reading is needed for the students. By having reading fluency, students can comprehend reading passage. In order to be fluent in reading, it is needed to have frequent practices. Repeated reading is as the main technique to have reading fluency. The students practice reading passages several times. The aim of this study is to discover students’ reading fluency through repeated reading. This study was a survey research. This study used a questionnaire consisting of closed-ended questionnaire and open-ended questionnaire. The results of this study were students got more fluent in reading by having several practices on repeated reading. The students read accurately the words and sentences in English with correct intonation. They also became more fluent in the pronunciation. While having repeated reading, the students improved vocabularies and understood the meaning of the words. Their comprehension of reading also increased.